Nonlinear dynamics of the CAM circadian rhythm in response to environmental forcing. (7th March 2015) - Hartzell, Samantha; Bartlett, Mark S.; Virgin, Lawrence; Porporato, Amilcare
Abstract: Crassulacean acid metabolism (CAM) photosynthesis functions as an endogenous circadian rhythm coupled to external environmental forcings of energy and water availability. This paper explores the nonlinear dynamics of a new CAM photosynthesis model (Bartlett et al., 2014 ) and investigates the responses of CAM plant carbon assimilation to different combinations of environmental conditions. The CAM model (Bartlett et al., 2014 ) consists of a Calvin cycle typical of C3 plants coupled to an oscillator of the type employed in the Van der Pol and FitzHugh–Nagumo systems. This coupled system is a function of environmental variables including leaf temperature, leaf moisture potential, and irradiance. Here, we explore the qualitative response of the system and the expected carbon assimilation under constant and periodically forced environmental conditions. The model results show how the diurnal evolution of these variables entrains the CAM cycle with prevailing environmental conditions. While constant environmental conditions generate either steady-state or periodically oscillating responses in malic acid uptake and release, forcing the CAM system with periodic daily fluctuations in light exposure and leaf temperature results in quasi-periodicity and possible chaos for certain ranges of these variables. This analysis is a first step in quantifying changes in CAM plant productivity with variables such as the mean temperature, daily temperature range, irradiance, and leaf moisture potential. Results may also be used to inform model parametrization based on the observed fluctuating regime. Abstract : Highlights: A recent model of CAM photosynthesis is coupled to changing environmental conditions. The circadian rhythm is shown to synchronize with external forcing. Bifurcations to periodic oscillations and complex behavior are identified. Environmental conditions for possible chaotic behavior are analyzed. The results extend the range under which CAM photosynthesis is expected to function.